The role of Baikonur in the context of militarypolitical cooperation between Kazakhstan and Russia - Chukalova, Ramilya; Kakenova, Zarina; Kushpaeva, Almagul; Alpeisov, Amirzhan; Kakenova, Galina (Opción, 2018)
The military partnership between Russia and Kazakhstan illustratethe multifaceted and mutually beneficial nature of relations between thitwo countries. In particular the joint use of the unique complex“Baikonur” is considered. Russia‟s leading role is shown in thepreparation of Kazakhstan‟s own space program. All these issues areconsidered on the basis of an analysis of the legal framework focooperation between the two states in the use of the BaikonuCosmodrome. Particular attention is paid to the problem of environmentasafety of the territory of the Republic of Kazakhstan associated with theoperation of the Baikonur Cosmodrome.